Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.25259/sni_40_2021
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous anterior cervicothoracic spinal epidural hematoma extending to clivus in SARS-CoV-2 infection

Abstract: Background: The treatment of spontaneous spinal epidural hematomas (SSEHs), depending on the lesion size and myeloradicular involvement, can be surgical or conservative. Here, we present a 55-year-old patient who sustained a SSEH several months following a systemic SARS-CoV-2 infection. Case Description: A 55-year-old immunocompromised female (i.e., history 17 years ago of Hodgkin’s lymphoma, nodular sclerosis variant) recently developed a SARS-CoV-2 infection treated with nonsteroidal anti-inflammatory ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…To our knowledge, this case is the first report of a chiropractor identifying SEH. As the patient had no specific risk factors for SEH and diclofenac is not associated with SEH to our knowledge [ 14 ], it seems possible given other similar recent studies [ 5 - 8 ] that his COVID-19 illness could have been a predisposing factor for SEH.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…To our knowledge, this case is the first report of a chiropractor identifying SEH. As the patient had no specific risk factors for SEH and diclofenac is not associated with SEH to our knowledge [ 14 ], it seems possible given other similar recent studies [ 5 - 8 ] that his COVID-19 illness could have been a predisposing factor for SEH.…”
Section: Discussionmentioning
confidence: 93%
“…According to a search of PubMed and Google Scholar on November 18, 2022, we identified four previously published cases of spontaneous SEH in patients following COVID-19 infection [5][6][7][8]. Several mechanisms have been suggested to explain these events, including venous thromboembolism, disseminated intravascular coagulation, increased pressure in the epidural venous plexus, and vasculitis [5][6][7], however, there is no clear unifying pathophysiological explanation. In addition, larger studies have identified an association between COVID-19 and other conditions involving bleeding such as intracranial hemorrhage and spontaneous muscle hematoma [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosuppression induced by the viral infection, the corticotherapy or immunomodulator agents are generally increasing the susceptibility for infections. Particularly for severe COVID-19 pneumonia, the respiratory disfunction associate increased intrathoracic pressure, microtrauma of the small vessels and haematomas of ligamental or muscular tissues, that could be favoured by the anticoagulant treatment [ 37 ]. The epidural vascular plexus is communicating with thoraco-abdominal venous vascularization and epidural or vertebral discs haematoma could be ruptured during the intense cough, with consecutive adjacent necrosis [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In adults, SSEH occurs with a frequency of 0.1 cases/100,000/year, and account for 0.6% of all spinal hemorrhages; in children, their incidence remains unclear. [ 19 , 31 , 34 ] Conservative treatment (i.e., infusion of recombinant coagulation factors, corticosteroids) may suffice where there are no major neurological deficits, while surgery is warranted for those with significant paresis. [ 4 , 6 , 8 ] Here, a 1-year-old hemophiliac male with a significant C5-T10 SSEH that contributed to a severe quadriparetic deficit warranted emergent surgical decompression.…”
Section: Introductionmentioning
confidence: 99%